1960
DOI: 10.1149/1.2427663
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of InAs, InP, GaAs, and GaP by Chemical Methods

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…The pressure of GaC18 is indeed negligible as shown by Seki and Araki (10). The absence of the dihalide has been assumed in previous discussions (10,13,15,16). The agreement observed in this study between the theoretical Ga/PCl3 ratio (neglecting GaC12) and the experimental value can be used as evidence that no significant amount of dichloride is present in the Ga-C1 system at 1200~ if the system studied was at equilibrium.…”
Section: Transport Mechanism--in a Recent Paper Seki Andsupporting
confidence: 84%
“…The pressure of GaC18 is indeed negligible as shown by Seki and Araki (10). The absence of the dihalide has been assumed in previous discussions (10,13,15,16). The agreement observed in this study between the theoretical Ga/PCl3 ratio (neglecting GaC12) and the experimental value can be used as evidence that no significant amount of dichloride is present in the Ga-C1 system at 1200~ if the system studied was at equilibrium.…”
Section: Transport Mechanism--in a Recent Paper Seki Andsupporting
confidence: 84%
“…The Growth of Pure Epitaxiat Layers of GaAs Choice o~ system.---It has been shown that Group III-V compounds may be prepared and transported by vapor phase reactions in a number of ways (1,12). In the case of GaAs the following systems are equivalent: (a) GaAs, HC1; (b) GaC18, Ga, As, H2; and (c) Ga, AsCI~, H2.…”
Section: Growth Of Sn-doped Layersmentioning
confidence: 99%
“…Iron (0.1 ppm) and chlorine (0.2 ppm) are the most noticeable impurities detected by the mass spectrometer. The effect of both these elements is uncertain although it has been shown in this laboratory that very high concentrations of chlorine can be tolerated in indium arsenide with little or no change in the measured electrical properties (10,11,12).…”
Section: Discussionmentioning
confidence: 96%